2015
DOI: 10.14720/aas.2014.103.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and sensory characteristics of jellies made from seven grapevine (Vitis vinifera L.) varieties

Abstract: Jellies of seven grapevine varieties were physico-chemical and sensorial characterized for the first time. Jellies differed significantly in moisture and ash contents, colour, pH, acidity and antioxidant activities. 'Tinta Carvalha' was the darkest and redness jelly, showing the highest antioxidant activity. Regarding sensory characteristics, no significant differences in the appearance, taste, sweetness, acidity and global assessment were observed among jellies. Nevertheless, these attributes were positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
1
Order By: Relevance
“…Singh and Chandra (2012) concluded that fruit jelly prepared with guava extract and carrot juice ratio of 75:25 was superior. On the contrary, this result differs from the study of Fernandes et al (2014), observed no significant differences in the appearance, taste, sweetness, acidity and global assessment but significant differences on color among 7 grape jellies.…”
Section: Color Taste Flavor and Texture Of Rind Jellycontrasting
confidence: 99%
“…Singh and Chandra (2012) concluded that fruit jelly prepared with guava extract and carrot juice ratio of 75:25 was superior. On the contrary, this result differs from the study of Fernandes et al (2014), observed no significant differences in the appearance, taste, sweetness, acidity and global assessment but significant differences on color among 7 grape jellies.…”
Section: Color Taste Flavor and Texture Of Rind Jellycontrasting
confidence: 99%
“…Simplex Centroid Design was used to generate ten experimental units from three ingredients (Cactus fruit juice (CFJ), M. oleifera Extract (MOE) and Table Sugar (TS)) using D-optimal Mixture design in Minitab version 16 statistical software. The lower and upper percentage values of the three ingredients (CFJ: 60%–80%, MOE: 0%–20%, and TS: 20%–40%) were determined considering previous research findings on jelly preparation ( Fernandes et al., 2015 ; Curi et al., 2017 ; Purba et al., 2018 ; Panchal et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%